2007
DOI: 10.1108/17410380810843444
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging automation and integration to improve manufacturing performance under uncertainty

Abstract: Purpose -This paper aims to address the differing impacts of automation and integration on manufacturing performance (MP) under different levels of environmental uncertainty. Design/methodology/approach -Responses from 303 companies are analyzed and presented. Findings -Under industrial (low uncertainty) environment, manufacturing system automation has significant positive impact on MP, while the impact of manufacturing system integration is not significant. Under post-industrial (high uncertainty) environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…Key reasons exist which emphasize the need for known technological infrastructure to support CE-DT integration. These include the turbulent and competitive markets [142] which industries and CE stakeholders operate from [140], the increasingly complex IT environment which organizations deal with, data complexity, and interconnected data networks [145]. In research to examine the technological infrastructure important for organizations which solely depend on information systems [142], the concept of "Process-Based Information Systems" or PBIS was developed.…”
Section: Technological Infrastructure Important For a Ce-dt Integrationmentioning
confidence: 99%
“…Key reasons exist which emphasize the need for known technological infrastructure to support CE-DT integration. These include the turbulent and competitive markets [142] which industries and CE stakeholders operate from [140], the increasingly complex IT environment which organizations deal with, data complexity, and interconnected data networks [145]. In research to examine the technological infrastructure important for organizations which solely depend on information systems [142], the concept of "Process-Based Information Systems" or PBIS was developed.…”
Section: Technological Infrastructure Important For a Ce-dt Integrationmentioning
confidence: 99%
“…Narasimhan and Kim (2002) investigated the moderating effect of market uncertainty in the relationship between planning integration and profitability, and found that profitability increased in markets with low uncertainty. Liao and Tu (2008) found that the integration of production processes had more impact on production performance under conditions of high environmental uncertainty. For these reasons, the hypotheses of the research are determined as follows.…”
Section: Extended Abstractmentioning
confidence: 99%
“…A set of actions that enables firms to achieve modularity in product design, production process design, and organizational design Ulrich and Tung (1991), Baldwin and Clark (1997), Feizinger and Lee (1997), Tu et al (2004) Manufacturing performance The level of attainment of various manufacturing objectives, which are commonly considered to include cost, quality, delivery, flexibility, and innovation Hayes and Pisano (1994), Boyer and Lewis (2002), Rosenzweig et al (2003), Swink and Nair (2007), Liao and Tu (2008)…”
Section: Modularity-based Manufacturing Practicesmentioning
confidence: 99%